Bus Driver Scheduling and Rostering: Maximise Fairness using Enhanced Harmony Search Algorithm with Varieties of Step Functions and Fret Spacing Formula - F. Mansor, N.; Abal Abas, Z.; S. Shibghatullah, A.; F.N. Abdul Rahman, A. (International Journal of Engineering and Technology, 2026)
This research proposes an adjustment of harmony search algorithm as a strategy to achieve a superior performance by manipulate three key operators in harmony search known as the Harmony Memory Consideration Rate (HMCR), Pitch Adjustment Rate (PAR) and Bandwidth (BW) that lead harmony search to accomplish a balancing between local exploitation and global exploration. The first contribution is having HMCR parameter using step function, while the second is applying the fret spacing concept on guitars toward BW parameter. There are three proposed models on the alteration of HMCR parameters based on the use of the fundamental step function; the constant interval of step function, dynamic increase and decrease interval functions. From an observation result, our proposed technique is superior adopted by using a second model that contrast to parameter adaptive harmony search (PAHS). In brief, this proposed technique magnificently to construct a fairer roster among drivers.